The Effect of Pressure Variations on the Characteristics of Coconut Shell Based Briquettes Using Tapioca Starch Adhesive - Devia Gahana Cindi Alfian; Marone J Tambunan; Fajar Paundra; Dicky J Silitonga; Lathifa Putri A; Muhammad Syaukani (ROTASI, 2023)
The very limited availability of energy on this planet is one of the main problems that concerns almost all countries. The presence of emergency energy indicates that energy usage is very high. Therefore, encouraging the use of new and sustainable energy sources is of utmost importance. Biomass energy can be the answer to overcoming the limitations of decreasing fossil assets, especially through the production of charcoal briquettes. Biomass energy is derived from plants or easily traceable natural materials that are abundant, such as wood waste, rice husks, bagasse, and coconut shells. Coconut shells, for example, can be a primary ingredient for making charcoal briquettes, using tapioca flour or starch as an adhesive. The briquettes can be produced using pressure variations of 50 kg/cm², 60 kg/cm², and 70 kg/cm², with a drying temperature of 100°C for 3 hours. The recommended ratio for making charcoal briquettes is 3 parts coconut shell to 1 parts tapioca flour adhesive. The purpose of this study is to compare the briquettes produced with coconut shell and tapioca flour adhesive to the SNI Briquette standard No.1/6235/2000. For the conducted tests, the results were as follows: the water content was 6.06%, the ash content was 5.9695%, the carbon content was 43.5946%, and the calorific value was 34,182.6808 calories. Additionally, the substance score yield was 26.845%, and the combustion rate was 0.12179 g/minute.